Epidemiyoloji, Biyoistatistik, Koruyucu Hekimlik ve Halk Sağlığı - Şahinöz, Saime; Torun, Perihan; Arıkan, İnci; Uğraş Dikmen, Asiye; Yılmazel, Gülay; Orman, Mehmet Nurullah; Suner Karakülah, Aslı; Doğan, İsmet; Sığırlı, Deniz; Gözükara Bağ, Harika Gözde; Korkmaz, Selçuk; Zararsız, Gökmen; et al. (2023)
-